2019
DOI: 10.3390/resources8010044
|View full text |Cite
|
Sign up to set email alerts
|

Financial Development and Bioenergy Consumption in the EU28 Region: Evidence from Panel Auto-Regressive Distributed Lag Bound Approach

Abstract: This paper investigates the relationship between financial development and bio-energy consumption in the European Union (EU28) countries for the period from 1990 to 2013 through the panel autoregressive distributed lag (ARDL) approach and causality analysis. The empirical results show that financial development shows a significant positive impact, at a 1% statistical level, on bio-energy consumption for the EU28 during the studied period. In developing countries, the financial market indicator affects bio-ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Financial development positively entices the growth of renewable energy consumption in BRIC nations, especially in the long run, which is align existing literature see, for instance, Shahbaz, et al [120]; Alsaleh and Abdul-Rahim [121], Liu, et al [122], and Burakov and Freidin [30]. Renewable energy has the potential to be a useful instrument in the pursuit of energy diversification through reduced reliance on fossil fuel supplies.…”
Section: Discussionmentioning
confidence: 67%
“…Financial development positively entices the growth of renewable energy consumption in BRIC nations, especially in the long run, which is align existing literature see, for instance, Shahbaz, et al [120]; Alsaleh and Abdul-Rahim [121], Liu, et al [122], and Burakov and Freidin [30]. Renewable energy has the potential to be a useful instrument in the pursuit of energy diversification through reduced reliance on fossil fuel supplies.…”
Section: Discussionmentioning
confidence: 67%
“…On the other hand, a sound stock market attracts new investors, which can mobilize extra resources to support energy investments and build reliance in the financial system that in turn increases energy requirement (Sadorsky 2010 ). For instance, Alsaleh and Abdul-Rahim ( 2019 ) found a positive nexus between financial markets and bio-energy consumption in developing countries whereas in developed countries, this relationship is positive for both financial markets and financial institutions.…”
Section: Relevant Literaturementioning
confidence: 99%
“…They used dynamic ordinary least squares (DOLS) method and concluded a positive and statistically significant of FD on REC. Alsaleh and Abdul-Rahim [26] examined the link between FD and bioenergy consumption in 28 European Union economies for the period of 1990-2013 by employing the panel ARDL approach. The results indicated that FD has a significant positive effect on bioenergy consumption.…”
Section: Literature Reviewmentioning
confidence: 99%